Organizacijų žinių vadybos sistemos: technologinis aspektas - Mačiuitis, Juozas; Mikalauskienė, Audronė Ona Ona; Zalieckaitė, Laima (Information & Media, 2008)
Žmogiškieji ištekliai yra daugelio organizacijų pagrindinis turtas. Darbuotojų žinios turi būti išsaugotos ir pereiti iš individualaus į organizacijos lygmenį, tuo užtikrinant organizacijos mokymosi procesą ir jos gerovės augimą. Žinių vadyba susideda iš įvairių komponentų ir aspektų, tokių kaip socialinis-kultūrinis, organizacinis ir technologinis. Šiame straipsnyje daugiau dėmesio skiriama technologiniam aspektui, apžvelgta programinė įranga, naudojama įvairiems žinių vadybos procesams palaikyti. Pateikti programinės įrangos pavyzdžiai pagal atliekamas pagrindines funkcijas, taip pat apžvelgtos kai kurios integruotos žinių vadybos sistemos.Knowledge management systems in organizations: technological aspectJuozas Mačiuitis, Audronė Ona Mikalauskienė, Laima ZalieckaitėSummaryKnowledge management is a hot topic in many business organizations. If properly applied, knowledge management may become a useful tool for business transformation and even the key to competitive advantage. Knowledge management is a very complex problem and can be tackled from several viewpoints: socio-organizational, financial and economical, technical, human, and legal. Knowledge management is essentially about facilitating the processes by which knowledge is created, shared and used in organisations. In this paper we address the technological aspect and survey available software systems that support different knowledge management activities. We categorize these tools into groups, based on their capabilities and functionality: document and content management tools, groupware and collaborative tools, taxonomy software, data mining and knowledge discovery tools, knowledge portals and networks, e-learning systems, intelectual property management tools, competence management tools, etc. We discussed samples of tools that represent what the market offers. We do not claim to cover the entire market, which is large, dynamic and expanding. Our research shows, that the most available tools are specialized, but some integrated suites exist too. To implement an efficient knowledge management system, organizations must identify their main problems, assign priorities, define strategy, and then select appropriate tools. Even though this paper focuses on tools, it is important to state that technology alone will never be the right solution to knowledge management. There are other components of knowledge management systems, and they are discussed in this paper. One popular and widely-used approach is to think of knowledge management in terms of three components: people, processes and technology. Another approach review the roles of knowledge management in learning organization from four perspectives: personal knowledge management, learning organization, organization culture, and organization corporate. Additionally, we present different ways of classifying knowledge management systems, and what requirements they must to meet.